Integrating Mogao Murals into souvenir design to preserve the cultural heritage of Dunhuang, China - Zhu, Qiuxia (2024)
Cultural product design has gained increasing attention as cultural tourism grows, with souvenirs emerging as vital tools for preserving cultural identity. However, the role of design in this preservation remains underexplored. This research addresses this gap by proposing an interdisciplinary framework, exploring how elements of the Mogao Murals can be integrated into souvenir design to support Dunhuang's heritage preservation and cultural sustainability. This research uses a qualitative case study to examine how three design firms collaborate with the Cultural Heritage Protection Department to create meaningful and viable souvenirs. Data from observations, document reviews, and semi-structured interviews with nine designers and two cultural experts provide insights into designers' roles, and thematic analysis is used to analyze the data. Findings show that designers' focus on ethics, consumer preferences, and adaptive challenges is crucial. Innovation, collaboration, and continuous learning are necessary for sustainable souvenirs. Aesthetic attributes, authenticity, and the cultural significance of Mogao Murals are key in the design process. Souvenirs are cultural preservation tools to balance commercial viability with cultural integrity, supported by internal cooperation and expert consultation. In conclusion, this research introduces the Framework of Souvenir Design for Cultural Heritage Preservation (FSDCHP), addressing a gap in the literature by examining how souvenir design supports cultural preservation. Positioned at the intersection of design and cultural preservation, it offers insights for design firms, institutions, and policymakers on integrating cultural elements into souvenirs while balancing commercial viability with respect for heritage. It also empowers communities by demonstrating how thoughtfully designed souvenirs can preserve cultural heritage, stimulate economic growth, and raise cultural awareness.